Nodal metastasis size predicts disease‐free survival in cutaneous head and neck squamous cell carcinoma involving the parotid but not cervical nodes. Issue 12 (11th November 2020) - Sood, Ashish; Wykes, James; McGuinness, John; Fowler, Allan; Ebrahimi, Ardalan
Abstract : Nodal metastatic size significantly predicts disease‐free survival on multivariate analysis, with the prognostic impact predominantly occurring in parotid metastases. Each 1 cm increase in the size of nodal metastasis increased the risk of recurrence or death by 27%. Parotid nodal metastasis size thresholds of <3, 3–4.5 and > 4.5 cm optimized prognostic discrimination. Abstract: Background: The 8th edition American Joint Committee on Cancer nodal (N) staging of cutaneous squamous cell carcinoma of the head and neck (cSCCHN) is largely based on lymph node metastasis size, despite conflicting data in the literature. This study aimed to investigate the prognostic significance of largest node size in cSCCHN. Methods: Retrospective analysis of 94 patients undergoing curative‐intent treatment for nodal cSCCHN with surgery ± radiotherapy at Liverpool Hospital, Sydney, Australia was conducted. Survival outcomes were assessed using multivariate Cox regression. The primary end point was disease‐free survival (DFS). Objective measures of model performance were used in exploratory analyses to identify optimal size thresholds for predicting survival. Results: Nodal metastasis size significantly predicted DFS on multivariate analysis (hazard ratio 1.24; 95% confidence interval 1.06–1.46; P = 0.008). This prognostic impact occurred predominantly in parotid metastases (hazard ratio 1.27; 95% confidence interval 1.07–1.51; P = 0.006); each 1 cm increase in size increased the risk of recurrence or death by 27%, irrespective of the number of involved nodes. In parotid metastases, size thresholds of ≤3, 3–4.5 and >4.5 cm optimized prognostic discrimination. Extranodal extension (ENE) was associated with decreased DFS in nodes ≤3 cm in size ( P = 0.025), but not in those >3 cm ( P = 0.744). Conclusion: Size is an important prognostic factor in cSCCHN with parotid metastases, with optimal thresholds of ≤3, >3–4.5 and >4.5 cm. The prognostic impact of ENE was seen only in nodal metastases ≤3 cm in size. These results may have important implications for node size thresholds and inclusion of ENE in the American Joint Committee on Cancer N staging categories.